A review on chemiresistive ZnO gas sensors - Mariane A. Franco; Patrick P. Conti; Rafaela S. Andre; Daniel S. Correa (Sensors and Actuators Reports, 2022)
Chemiresistive gas sensors have been widely applied to monitor analytes of environmental, food and health importance. Among the plethora of materials that can be used for designing chemiresistive sensors, ZnO is one of the most explored for gas sensing, as this material has a low-cost, is non-toxic and can be easily obtained through standard chemical synthesis. Adding to this, ZnO can form heterostructures capable to improve sensor performance regarding sensitivity, selectivity and stability. Moreover, ZnO heterostructures also contribute to lower operating temperature of gas sensors, since the synergistic effects contribute to amplify the sensor signal. In this review, we survey recent advances on different types of chemiresistive ZnO-based gas sensors, focusing on how the morphology and structure of these materials influence on the sensor response. Challenges and future perspectives for ZnO chemiresistive sensors are also discussed.